Consideration of Abiotic Natural Resources in Life Cycle Assessments - Mario Schmidt (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book contains a collection of articles dealing with how the extraction of mineral resources can be considered in environmental analyses such as Life Cycle Assessment (LCA). The consumption of resources, e.g., metals, is increasing strongly worldwide. This is associated with more energy use; environmental pollution; and social, economic, and political consequences. An increase is also expected for the coming decades. At the same time, modern products and technologies, even in the field of renewable energies, require a large number of critical raw materials. A crucial question here is the exhaustibility of natural resources. What is the relevance of resource depletion today? Must a geological shortage of metals be expected in the foreseeable future? How could such a thing be considered in the LCA of products and weighed against other environmental aspects? The articles in question have been written over the past three years by leading experts in both geology and environmental sciences and show the breadth of the controversial discussion.